Place Attachment and Destination Loyalty of Religious Tourists in Chiang Mai, Thailand: Examining the Role of Emotional Solidarity and Risk Perception - Ruttanavisanon, Waret; Agmapisarn, Charoenchai (Thammasat Review, 2022)
Religious tourism is a term that refers to contemporary travel patterns to religiously themed tourist destinations when tourists satisfy their religious and/or recreational needs. The growth of religious tourism is inextricably linked to the worldwide increase in spiritual searching by individuals of all ages, cultures, and religions. Religious destinations are places of development, commitment, and vitality, yet they often attract attention for their emotional significance. This research investigates tourists’ destination loyalty through the perspectives of their emotional connection to the place, their emotional solidarity with locals, and their risk perception. Based on data collected from 543 Thai domestic tourists to Chiang Mai’s temples, it was founded that place attachment had a direct effect on emotional solidarity. Moreover, it was shown that emotional solidarity is a significant predictor of destination loyalty. Additionally, it was demonstrated that the significant mediated relationships between place attachment and destination loyalty through the three aspects of emotional solidarity. Furthermore, the tourists’ risk perception of Chiang Mai during the COVID-19 epidemic indicated that the moderating relationships between emotional solidarity and destination loyalty was insignificant. Several managerial implications for DMOs are suggested by this research.